Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/hdy.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a coastal fish in the Azores: recent colonisation or sudden expansion of an ancient relict population?

Abstract: The processes and timescales associated with ocean-wide changes in the distribution of marine species have intrigued biologists since Darwin's earliest insights into biogeography. The Azores, a mid-Atlantic volcanic archipelago located >1000 km off the European continental shelf, offers ideal opportunities to investigate phylogeographic colonisation scenarios. The benthopelagic sparid fish known as the common two-banded seabream (Diplodus vulgaris) is now relatively common along the coastline of the Azores arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…Although the results from the slow evolving S7 gene do not show such a clear cut, Azores keeps its singularity, being isolated (with no migration) from the remaining European locations (average Nm of 0.160 between Azorean locations and the remaining ones). Similar findings related to the peripheral position of Azorean haplotypes were also reported for several other species [62,68]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the results from the slow evolving S7 gene do not show such a clear cut, Azores keeps its singularity, being isolated (with no migration) from the remaining European locations (average Nm of 0.160 between Azorean locations and the remaining ones). Similar findings related to the peripheral position of Azorean haplotypes were also reported for several other species [62,68]. …”
Section: Discussionsupporting
confidence: 90%
“…This trend for the genetic isolation of the Azores can be occasionally reversed by severe or atypical weather events (e.g. [68]).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the marginal and isolated position of the Azores (approximately 1500 km from mainland Portugal), this result is rather unexpected. Many genetic studies on fishes reported strong genetic segregations of Azores’ population from continental ones [58]. However, we cannot disregard that only two haplotypes, one of which a singleton, were sampled in individuals from this archipelago.…”
Section: Discussionmentioning
confidence: 95%
“…These islands, just off the coast of Europe and Africa, are formed by volcanic seamounts and were never part of a continent. This makes the biogeography of the islands very attractive for phylogeographic studies (Quinteiro et al, ; Stefanni et al, ; Whittaker, ). The marine environment is very often characterised as having complex oceanic currents and no physical barriers, which greatly increase a species’ dispersal potential, promoting high gene flow over large scales (Selkoe et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several phylogeographic studies have reported a low population genetic differentiation in the Macaronesian region for different taxa, including gastropods (De Wolf et al, ), crustaceans (Faria et al, ; Quinteiro et al, ) and fishes (Francisco et al, ; Stefanni et al, ). On the other hand, the Macaronesia archipelagos are also characterised by different upwellings zones, habitat discontinuities and ecotones between areas with different environmental properties and areas with historical sea level drops ( e.g ., Stefanni et al, ). These features seem to be responsible for maintaining discrete subpopulations over a species’ range, suggesting stable currents in Macaronesia that promote these genetic differences.…”
Section: Introductionmentioning
confidence: 99%